Legion Of Honor (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1932)
Truman H. Aldrich W. Lawrence Austin W. S. Ayres John Henry Banks Wrn de L Benedict Andrew A Blair Walter M. Brodie H. H. Burden Charles Butters